Micro- and Nano-Plastics in Drinking Water: Threat or Hype? Critical State-of-the-Art Analysis of Risks and Approaches - Andrea G. Capodaglio (Journal of Xenobiotics, 2025)
Microplastic (MP) contamination affects all environmental media, even in remote, unpopulated regions of the globe. Many studies have addressed this issue under various aspects; however, actual and definitive evidence that MPs are a cause of human health risk in actual environmental conditions has not been provided. MP decomposition generates smaller nanoplastics (NPs) with different properties, closer to engineered nanoparticles than to MP. Their detection is more complex and laborious than MP’s, and, as such, their fate and effects are still poorly studied. Advanced technologies to remove MP/NPs from supply water are being investigated, but current evidence indicates that conventional drinking water treatment facilities efficiently remove a major part of MPs, at least as far as sizes greater than 20 µm. Notwithstanding recent developments in MP/NP classification and detection techniques, at the moment, very few studies specifically address NPs, which, therefore, deserve more targeted investigation. This paper addresses MPs and NPs in drinking water, examining recent current literature on their presence and state-of-the-art in risk assessment and toxicology. The paper also critically overviews treatment technologies for their removal and discusses the present knowledge gap and possible approaches to this widespread issue.